Beyond the box : B.F. Skinner's technology of behavior from laboratory to life, 1950s-1970s - Rutherford, Alexandra, 1971- (Toronto [Ont.] : University of Toronto Press, 2009)
Beyond the Box is the first full-length study of the ways in which Skinner's ideas left the laboratory to become part of the post-war public's everyday lives, and chronicles both the enthusiasm and caution with which this process was received.
Introduction: beyond the box -- A visible scientist: B.F. Skinner as public intellectual -- From pigeons to people: constructing the human Skinner box -- Conditioning a cure: behavior modification in the mental institution -- Crime and punishment: contingency management in the prison system -- How to really win friends and influence people: Skinnerian principles in self-help -- Living the dream: Walden Two and the laboratory of life -- Conclusion: from laboratory to life.
Includes bibliographical references (pages 177-196) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
JSTOR
Keywords: Skinner, B. F. -- 1904-1990.; Skinner, B. F -- 1904-1990.; Skinner, B. F. -- 1904-1990.; Skinner, B. F. -- 1904-1990; Behaviorism (Psychology); Behaviorism -- history; History, 20th Century; Behaviorism; Béhaviorisme (Psychologie); Médecine -- Histoire -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; PSYCHOLOGY -- Movements -- Behaviorism; MEDICAL -- History; Behaviorism (Psychology)